Actionability of Climate Services in Southeast Asia: Findings from ACIS baseline surveys in Vietnam, Lao PDR and Cambodia - Coulier, Miguel; Carter, Anoushka; Tuan Minh Duong; Tam Thi Le; Giang Thi Thu Luu; Madsen, Erik Junge (2018)
The baseline study under the project, “Agro-Climate Information Services for women and ethnic minority (ACIS) farmers in Southeast Asia,” strongly suggests that climate services must better suit farmers’ needs of climate information. In this Info note, the actionability of climate services can be improved by looking at the following factors: availability, accessibility, timeliness, understandability, and usefulness. Based on these factors, the study revealed that climate services are available in all countries covered by the ACIS project. However, issues on accessibility surfaced in the conduct of the study. Ethnic minority women are in the risk of experiencing particular marginalization, in particular due to language and extensionists more often meet men. Aside from accessibility issues, the study found that meteorologists and extension officers lack the necessary skills to package climate services in a more understandable manner for farmers.